Institutional analysis of financial market fragmentation in Sub-Saharan Africa: A risk-cost configuration approach - Machiko Nissanke; Ernest Aryeetey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The paper examines the source of financial market fragmentation in sub-Saharan Africa in the framework of institutional economics. Based on fieldwork data from Ghana, Malawi, Nigeria, and Tanzania, it analyses financial risk management, the transaction costs for loan screening and monitoring, and contract enforcement. It shows how, faced with various institutional constraints, the range of clientele selected by formal and informal lenders becomes both narrow and at the extreme market-ends. It evaluates the prevailing state of managing risks for market structure, and binding institutional constraints for market transformation and deepening in sub-Saharan Africa.
Keywords: O16; O17; D49; R51; 330; financial markets; institutions; risk-cost analysis; sub-Saharan Africa; Finanzmarkt; Institutionalismus; Zentralafrika